Lesbianidades e as referências legitimadoras da sexualidade - Toledo, Lívia Gonsalves [UNESP] (2010)
This article is part of a master's degree dissertation that studied the way as stigmas and stereotypes regarding lesbianity influence the life, in the sphere of the sexuality, of women that denominate themselves as lesbians, resident in a city in the interior of the State of São Paulo. The stigma here analyzed is that lesbians are women that frustrated with men. We tried to show, through the narratives of the research s participants and basing on gender and feminist studies, how the heteronormativist system naturalizes the masculinity to the men and the sexuality in the masculinity, and how it legitimates speeches about lesbian woman through the heterosexual referential. Also, we tried to show some strategies of the biopoder for the maintenance of that system and, starting from interviews in depth, we presented how the participants of the research (lesbian women) make speeches on that stigma and how they re-significate it through their own narratives. That research was financed by Fundação de Amparo à Pesquisa do Estado de São Paulo FAPESP, and accomplished by the Pos-Graduation Program of the Universidade Estadual Paulista Campus of Assis-SP.Key words: Gender. Sexuality. Lesbianity. Heteronormativity.